Pengetahuan dan Sikap Remaja dala Upaya Pencegahan HIV/AIDS - Priscilla Donmiana Vidiyanti (Journal of Ners and Midwifery, 2015)
Teenagers are the vulnerable group of contracting HIV because of changes in the reproductive organs are more mature in adolescents, causing a boost sexual arousal and stronger in her teens. The purpose of this study was to describe the knowledge and attitudes of adolescents in the prevention of HIV/AIDS. The method used descriptive, a population of this research is all student on second grade of catholic high school students of Diponegoro Blitar were 219, the samples size was 65 students using systematic random sampling techniques, and use of a questionnaire. The results showed knowledge in the prevention of adolescent HIV/AIDS some 66% (43 students) had good knowledge. The attitude of young people in the prevention of HIV/AIDS some 52% (34 students) had a positive attitude, because all student have given health promotion about HIV/AIDS. Recommendations of this study are expected to conduct health promotion officer of health promotion, education materials that expand the knowledge and attitudes of adolescents can develop better and will affect the health status of adolescents.